METB-10. EVALUATION OF NON-SUPERVISED MATRIX-ASSISTED LASER DESORPTION / IONIZATION MASS SPECTROMETRY IMAGING (MALDI) MASS SPECTROMETRY IMAGING (MSI) COMBINED WITH MICROPROTEOMICS FOR DETERMINATION OF GLIOBLASTOMA HETEROGENEITY. Issue 11 (6th November 2017) - Le Rhun, Emilie; Duhamel, Marie; Drelich, Lauranne; Zairi, Fahed; Reyns, Nicolas; Wisztoski, Maxence; Maurage, Claude Alain; Escande, Fabienne; Salzet, Michel; Fournier, Isabelle
Abstract: The aim of the GLIOMIC study (NCT 02473484) is to identify prognostic subgroups of glioblastoma by Matrix-assisted laser desorption/ionization mass spectrometry imaging (MALDI-MSI) followed by tissue micro-extraction and unsupervised clustering. In this analysis, lipid MALDI imaging was performed for 18 glioblastoma samples, peptide MALDI imaging for 29 samples and microproteomic analysis for 6 samples. Frozen tissue sections of 12 µm thickness were obtained followed by trypsin digestion and by matrix deposition with a sprayer. Tissues were prepared for imaging of peptides and lipids. Tumor-specific mass spectra were acquired with 70 µm spatial resolution. After molecular image acquisition, matrix was removed, and tissues were stained and annotated by a pathologist. The imaging datasets were spatially segmented by clustering all spectra by their molecular profile similarity. Then the regions of interest were determined and tissue microextraction was performed followed by shot gun analysis for the identification of proteins and molecular pathways. There was intratumoral heterogeneity as well as a heterogeneity between pathologist annotation as viable tumor, necrosis or infiltration zone, and lipid/peptide imaging. Four main groups of tumors were identified after unsupervised lipid or peptide MALDI imaging. Regions of interest defined by these 2 imaging techniques correlated only partially. Ten patients have died. Actuarial median overall survival was 513, 5 days (n=3), 638 days (n=6), 709 days (n=3) and 856 (n=2) in the lipid-defined –groups, and 312 days (n=4), 463 days (n=7), 674.5 days (n=10) and 813 days (n=5) in the peptide-defined groups. Microproteomic analyses showed that one pattern is associated with cell division processes and associated with a more aggressive phenotype. In conclusion, MALDI MSI combined with microproteomics may allow the identification of new subgroups of glioblastoma and may provide new information on glioblastoma heterogeneity.